Conceptually Redefining Neonatal Palliative Care. (June 2020) - Kain, Victoria J.; Chin, Susan D.
Abstract : Background: First defined in 2002 by Catlin and Carter, neonatal palliative care (NPC) is a relatively new model of care in neonatal pediatrics, first appearing in the medical literature in the early 1980s. Purpose: The purpose of this article is to suggest a conceptual definition of NPC that encompasses all the essential concepts as a way of moving NPC forward by having a consistent approach. Methods: Following a review of the NPC literature, a thematic analysis as a method for identifying, analyzing, and interpreting patterns of meaning in the definitions ("themes") within the literature was undertaken. Findings: The major themes identified included philosophies of care, support, culture and spirituality, the team, and clinical management. Implications for Research: At the heart of NPC is the primacy of maintaining quality of life, while providing ethical and humane care that supports a "good death." The extensive elements presented in this article are considered essential to a comprehensive and conceptual definition of NPC proposed here.